2012
DOI: 10.1117/12.917312
|View full text |Cite
|
Sign up to set email alerts
|

Targeting biological sensing with commercial SERS substrates

Abstract: There is an increasing need for rapid and accurate detection, identification, and quantification of chemical, biological, and energetic hazards in many fields of interest. To meet these challenges, researchers are combining spectroscopy with nanoscale platforms to create technologies that offer viable and novel solutions for today's sensing needs. One technology that has gained increasing popularity to meet these needs is surface enhanced Raman scattering (SERS). For ideal SERS sensing, commercially available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 91 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Raman and Raman-based detection systems rely on specific vibrations within a molecule from which a fingerprint spectrum is produced 14,60,78,79,[81][82][83][84][85][86][87][88][89][90][91][92] . This fingerprint spectrum can be used for the identification, and in some cases quantification, of unknown materials.…”
Section: Brief Review Of Some Current Techniques Utilized For the Detmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman and Raman-based detection systems rely on specific vibrations within a molecule from which a fingerprint spectrum is produced 14,60,78,79,[81][82][83][84][85][86][87][88][89][90][91][92] . This fingerprint spectrum can be used for the identification, and in some cases quantification, of unknown materials.…”
Section: Brief Review Of Some Current Techniques Utilized For the Detmentioning
confidence: 99%
“…Since there have been so many examples of fabricated SERS substrates being flexible in material and application, it is important to also discuss examples of specific form and functionality being incorporated into these SERS substrates. One recent literature example was conducted by a group out of Washington University 17,84,92,131,[156][157][158][159][160][161][162] in which specifically designed nanoparticles, referred to as nanorattles, were incorporated into filter paper resulting in a SERS active flexible substrate surface. Please see Figure 7A for example TEM images of the nanorattles.…”
Section: Examples Of Flexible Sers Substrates (Flexible Materials and mentioning
confidence: 99%
See 1 more Smart Citation
“…36 Successful implementation of bifunctional peptides in a sensing platform designed for the selective recognition of hazardous materials has been previously demonstrated. 44 This system employed surface enhanced Raman scattering (SERS) for hazard detection. SERS-based techniques and platforms can combine traditional spectroscopy with nanotechnology.…”
Section: Peptide-based Sensingmentioning
confidence: 99%
“…It is suggested that the reader look to several comprehensive reviews and interesting papers for a more complete discussion of SERS substrate fabrication techniques, applications, advantages and challenges. 1,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] One of the more common and easily achieved methods for the fabrication of SERS substrates is known as the drop and dry technique. Drop and dry techniques or Film over Nanosphere (FONS) offer some advantages as compared to other fabrication methods like ease of fabrication due to cheaper manufacturing materials, and often being lower cost in skill, time and overall materials as compared to some other more fabrication intensive techniques.…”
Section: Example Sers Substratesmentioning
confidence: 99%